A Review of Career Assessment Tools - Firkola, Peter (Archives of Business Research, 2021)
This paper provides an overview of career assessment tools. Background on key career concepts is first introduced. A number of career assessment tools are then examined. These assessment tools included reviewing personal history, interest inventories, values assessments, personality assessments, and aptitude tests. The importance and limitations of these career assessment tools are then discussed.